Intentional Weight Loss and Obesity-Related Cancer Risk - Luo, Juhua (JNCI Cancer Spectr, 2019)
BACKGROUND: Epidemiologic studies regarding weight loss and subsequent cancer risk are sparse. The study aim was to evaluate the association between weight change by intentionality and obesity-related cancer incidence in the Women’s Health Initiative Observational Study. Eleven cancers were considered obesity related: breast, ovary, endometrium, colon and rectum, esophagus, kidney, liver, multiple myeloma, pancreas, stomach, and thyroid. METHODS: Postmenopausal women (n = 58 667) aged 50–79 years had body weight and waist circumference (WC) measured at baseline and year 3. Weight or WC change was categorized as stable (change < ±5%), loss (≥5%), and gain (≥5%). Self-report at year 3 characterized weight loss as intentional or unintentional. During the subsequent 12 years (mean) of follow-up, 6033 incident obesity-related cancers were identified. Relationships were evaluated using multivariable Cox proportional hazards regression models. RESULTS: Compared to women with stable weight, women with intentional weight loss had lower obesity-related cancer risk (hazard ratio [HR] = 0.88, 95% confidence interval [CI] = 0.80 to 0.98). A similar result was observed for intentional WC reduction (HR = 0.88, 95% CI = 0.80 to 0.96). Among all cancers, intentional weight loss was most strongly associated with endometrial cancer (HR = 0.61, 95% CI = 0.42 to 0.88). Intentional WC loss was also associated with lower colorectal cancer risk (HR = 0.79, 95% CI = 0.63 to 0.99). Unintentional weight loss or weight gain was not associated with overall obesity-related cancer risk. CONCLUSION: Intentional weight or WC loss in postmenopausal women was associated with lower risk of obesity-related cancer. These findings suggest that postmenopausal women who intentionally lose weight can reduce their obesity-related cancer risk.